Konflik pada Tempat Kerja Berdasarkan Gaya Kepemimpinan Toxic di Perguruan Tinggi: Systematic Literature Review - Febrisi Dwita; Leony Agustine; Supardi Supardi; Shalahuddin Shalahuddin (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
There have been many studies discussing toxic leadership styles, and their impact on organizational culture, missions, and individuals. However, it is rare to find explicit discussions about toxic leadership styles, especially in a complex and comprehensive manner in education, especially universities/universities. The term "toxic leadership" was first introduced in 1996 (Whicker, 1996), where it began to discuss the role of influencing leadership culture in business and military institutions. However, empirical literature began to be carried out in 2007 (Padilla et al., 2007) which linked leadership with the concept of the Higher Education system with the phenomenon of "social learning". To better understand the development process regarding this variable which was carried out in 2000 at this time, the author will use a systematic literature review analysis of previous research regarding the influence of toxic leadership in tertiary institutions from three different perspectives including: 1). How to understand toxic leadership in influencing organizational culture? 2). How to understand toxic leadership in influencing employee morale (morale) in college? as well as 3). Examine the role of toxic leadership in shaping the work environment of employees, so as to improve performance in an organization.